Remapping Hydroecoregion Boundaries: A Proposal for Improving the Base of the Running Water Monitoring Procedures - Lorenzo Traversetti,; Alessandro Manfrin ,; Massimiliano Scalici, (Journal of Basic & Applied Sciences, 2013)
Inland waters are constituted by a lot of seriously threatened habitats. The increasing need to safeguard these ecosystems led European Union Member States to propose the Water Framework Directive which decided the creation of homogeneous areas characterized by very similar geology, topography and climate, known as hydroecoregions (HER) and firstly proposed by the French National Research Institute of Science and Technology for Environment and Agriculture (Cemagref). Watercourses reference conditions had to be defined within any HER in order to confront any sampling site. HERs are consistent with European scale maps but important local reinterpretations in order to define more precise boundaries and extensions for each hydroecoregion are required and this point constitutes the main goal of this manuscript. Latium is a climatically very homogeneous region and it’s roughly divided into three major portions confirming Cemagref’s proposal. Geological and topolographical maps were then used in order to achieve a more detailed characterization of this region in order to obtain a more defined map. All our results allow to better define similarities and differences both between streams and within the same stream allowing to entirely locate each water course within the same HER. It would be important to follow up this study by proposing a similar approach for the entire national territory based on an appropriate region knowledge.